Phaeochromocytoma with hypercortisolism and hypercalcaemia. (7th October 2015) - Edafe, Ovie; Webster, Jonathan; Fernando, Malee; Vinayagam, Ragu; Balasubramanian, Sabapathy P
Abstract : We report a case of phaeochromocytoma associated with hypercortisolism and hypercalcaemia in a 62-year-old man. The patient presented to clinic, with a 3-year history of exertional headaches, and a 4-month history of increasing fatigue, sweating and palpitations, loss of appetite and weight, and sleepiness. He did not have a medical, family or social history that could account for these symptoms. 24 h urinary catecholamines, plasma metanephrines, 24 h urinary cortisol and adjusted serum calcium, were elevated. Overnight low-dose dexamethasone suppression test did not suppress morning plasma cortisol. Serum intact parathyroid hormone and parathyroid hormone-related peptide were low, and adrenocorticotropic hormone was normal. The patient was treated with intravenous 0.9% sodium chloride and disodium pamidronate to control hypercalcaemia. CT showed a 10 cm left adrenal mass. Following inpatient treatment with phenoxybenzamine, he underwent a left adrenectomy and histology confirmed a phaeochromocytoma. Postoperatively, he required long-term steroids for contralateral adrenal suppression. Adjusted serum calcium returned to normal postoperatively.